2016
DOI: 10.1097/wnr.0000000000000701
|View full text |Cite
|
Sign up to set email alerts
|

Sex-specific and genotype-specific differences in vocalization development in FMR1 knockout mice

Abstract: Fragile X Syndrome (FXS) is a neurodevelopmental disorder caused by a trinucleotide (CGG) hyperexpansion in the FMR1 gene, functionally silencing transcription of the fragile x mental retardation protein (FMRP). This disorder is characterized by impaired cognition, communication, and social behavior. The purpose of this study was to investigate the development of ultrasonic vocalization (USV) behavior in a FMR1 deficient mouse model. On postnatal days (PD) 9–14, separate cohorts of FVB/NJ pups were removed fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
29
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 16 publications
2
29
0
Order By: Relevance
“…Recent experimental evidence has also shown that female Fmr1 KOs present normal fear learning and anxiety, but show impaired fear memory (Nguy & Tejada‐Simon, 2016). Furthermore, analysis of behaviors at different ages has shown sex‐specific differences in ultrasonic vocalization production (Reynolds, Nolan, Jefferson, & Lugo, 2016), though other strains have not shown this effect (Gauducheau et al., 2017). In a recently published review, authors summarized the effects of Fmr1 deletion across both male and female mice, noting that some behaviors have sex‐specific effects, though most behaviors have not yet been examined in females (Romano, Cosentino, Laviola, & De Filippis, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Recent experimental evidence has also shown that female Fmr1 KOs present normal fear learning and anxiety, but show impaired fear memory (Nguy & Tejada‐Simon, 2016). Furthermore, analysis of behaviors at different ages has shown sex‐specific differences in ultrasonic vocalization production (Reynolds, Nolan, Jefferson, & Lugo, 2016), though other strains have not shown this effect (Gauducheau et al., 2017). In a recently published review, authors summarized the effects of Fmr1 deletion across both male and female mice, noting that some behaviors have sex‐specific effects, though most behaviors have not yet been examined in females (Romano, Cosentino, Laviola, & De Filippis, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Similarly deviant vocalizations have also been observed in Fmr1‐ and Tsc1‐ deficient pups, therefore our results contribute to a consistency of communication deficits found across several mTOR models (Reynolds et al., 2016; Tsai et al., 2012; Young, Schenk, Yang, Jan, & Jan, 2010). Specifically, Fmr1 KO pups were shown to emit significantly fewer vocalizations than their WT counterparts when separated from their mother (Reynolds et al., 2016). In contrast, Tsc1 HT pups emitted significantly more vocalizations than their controls (Tsai et al., 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Both male and female Fmr1 KO pups have been shown to exhibit a decreased call duration when compared with wild types, resembling our findings in this study (Reynolds et al., 2016). Call duration is significant as dams have been shown to prefer a longer call over a shorter one (Smith, 1976).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[5][6][7][8][9][10] Given that the Fmr1 mutation is an X-linked mutation, females with the mutation are typically heterozygous and the functional copy of the gene is still expressed throughout the body. 18,19 These prior studies show communication alterations in male and female Fmr1 mutants, therefore helping to elucidate the impact of sex. However, when studies compare male and female mice with full loss of Fmr1, there are still sex differences in their behavioral phenotype, suggesting that gene dosage effects are not the only factor involved.…”
mentioning
confidence: 93%